PENGARUH PERSEPSI PELAKSANAAN SENSUS PAJAK NASIONAL, PENGETAHUAN PERATURAN PERPAJAKAN, DAN KESADARAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DI DAERAH ISTIMEWA YOGYAKARTA - Ana Choirun Nisa; Andri Waskita Aji (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2014)
This research is aimed to know the influence of perception of Sensus Pajak Nasional, knowledge of taxation laws, tax awareness to tax compliance in the Special Region of Yogyakarta. This research uses purposive sampling and survey methods with questionnaires. Questionnaires distributions to 100 respondents. The respondents of this research are taxpayer sespecially business owners who are in the business districtand have stickers of Sensus Pajak Nasional. Data analysis was performed using multiple linear regression analysis with SPSS 19 for windows. The results of this research indicated that perception of Sensus Pajak Nasional have a positive and significant influence on taxpayer's complience, knowledge of taxation laws tax awareness have a positive and significant influence on taxpayer's complience. The magnitude of perception of Sensus Pajak Nasional, knowledge of taxation laws, tax awareness to tax compliance to explain tax compliance is 83,3%, while the remaining 16,7% explained by other variables not examined in this research. Keyword: the perception of Sensus Pajak Nasional, knowledge of taxation laws, tax awareness, taxpayer's compliance